Odpowiedzi

2009-10-18T18:34:02+02:00

½x-3y= 1 ⅔
⅓x - ⅔y = -²₉ / +⅔y

½x-3y= 1 ⅔
⅓x= -²₉+⅔y / *3

½x-3y= 1 ⅔
x = -⁶₉ + ⁶₃y

½x-3y= 1 ⅔
x = -²₃ + 2y

½ * (-²₃ + 2y) - 3y = 1 ⅔
x = -²₃ + 2y

-²₆ + y - 3y = 1 ⅔
x = -²₃ + 2y

-²₆ - 2y = 1 ⅔ / +²₆
x = -²₃ + 2y

-2y = 1⁴₆ + ²₆
x = -²₃ + 2y

-2y = 2 / :-2
x = -²₃ + 2y

y=-1
x = -²₃ + 2y

y=-1
x= -²₃ + 2 * (-1)

y=-1
x= -²₃ -2

y=-1
x=-2²₃


Chodziło o to??
Czy o to:

½x-3y= ½ * ¹₃ - 3 * - ½ = ¹₆ +³₂ = ¹₆ + ⁹₆ = ¹⁰₆ = 1⁴₆ = 1²₃
⅓x - ⅔y = ⅓ * ⅓ - ⅔ * (- ½) = ¹₉ +²₆ = ¹₉ + ⅓ = ¹₉ + ³₉ = ⁴₉